Mathematical validation of measurement of root fracture resistance: an in vitro study - Rafat Bagheri; Abbas Abbaszadegan; Mohammad R. Nabavizadeh; Maryam Ferooz; Peter Parashos (BMC, 2021)
Abstract Background The aim of this study was to develop a mathematically valid method of assessing fracture resistance of roots. The model developed used mesial roots of lower molars instrumented using stainless steel hand files (SS) and two rotary nickel-titanium (NiTi) systems. Methods Eighty human lower molars were selected and randomly divided into four groups (n = 20). After instrumentation, the root canals were obturated using thermoplasticized gutta percha. The roots were covered with a simulated periodontal ligament and mounted vertically in autopolymerizing acrylic in PVC tubes. Using a universal testing machine, the force to fracture (N) was applied and the maximum load (FL) was recorded. Remaining dentine volume was calculated and the fracture resistance (FR) was recorded. The data were analyzed using SPSS version 22 with P < .05. Results There were no significant differences among the instrumentation methods for FL but in FR the roots instrumented using rotary NiTi showed significantly lower values than control groups and SS files (P < 0.001). Conclusions Considering the effect of root length, volume of the root, and volume of the instrumented canal as well as the maximum failure load may be a more objective method of reporting fracture resistance of roots.